Micro-health insurance in dentistry: the road less travelled - Hakeem, Naz-E-Farha; Eshwar, Shruthi; Srivastava, B. K.; Jain, Vipin (International Journal Of Community Medicine And Public Health, 2019)
Oral health is indeed a challenge for the urban poor. Majority of the patients spend from their pocket, which aggravates their financial condition. It is paramount for the government and the healthcare industry to adopt a value-based approach to redress the oral health lapses for the underserved population. Micro health insurance (MHI) can have a game changing effect on the oral healthcare space too, if concerned stakeholders build the right partner network. Aim of the study was to discuss the principal features, basic structure, and functioning of a few MHI schemes, and presents a hypothetical model of MHI which can be implemented in dentistry. Literature search was conducted in two main databases, pubmed and cochrane, using key phrases such as “community based health insurance,” “micro health insurance,” micro or community based health insurance,” and “health insurance and financial protection”. Articles published in last ten years with full texts were considered. 23 schemes were eligible for the systematic review. Our analysis shows that MHI, in the majority of cases, contributes to the financial protection of its beneficiaries, by reducing out of pocket health expenditure, catastrophic health expenditure, household borrowings and poverty. However, the studies did not affirm oral health benefits. The importance of oral healthcare in India is superficial. Focus on oral healthcare can be achieved only if the impending cost due to out of pocket payments can be supplanted with a more affordable and dynamic payment model. With MHI extended to oral healthcare, India can certainly achieve its SDG goal. It’s time to look beyond.